2021
DOI: 10.1186/s12967-021-02885-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of LncRNAs expression profiles in an in vitro model of steatosis treated with Exendin-4

Abstract: Background and aims The hallmark of non-alcoholic fatty liver disease (NAFLD) is the excessive hepatic lipid accumulation. Currently, no pharmacotherapy exists for NAFLD. However, the glucagon-like peptide-1 receptor agonists have recently emerged as potential therapeutics. Here, we sought to identify the long non-coding RNAs (LncRNAs) associated with the steatosis improvement induced by the GLP-1R agonist Exendin-4 (Ex-4) in vitro. Methods Steatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…On the other hand, H19 was downregulated ( Figure 3B ). This is in line with the finding of Khaoula et al who showed a decreased expression of lncRNA H19 in an HepG2 steatotic model ( 43 ). However, our findings oppose the result of Liu et al which reported an induction of H19 upon FA treatment.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, H19 was downregulated ( Figure 3B ). This is in line with the finding of Khaoula et al who showed a decreased expression of lncRNA H19 in an HepG2 steatotic model ( 43 ). However, our findings oppose the result of Liu et al which reported an induction of H19 upon FA treatment.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that the incubation of HepG2 cells with 400 µM OA after 6 h of starvation induces steatosis, as reflected by the presence of lipid droplets [ 39 , 40 ]. We have further shown that treatment of the steatotic HepG2 cells with 200 nM Ex-4 for 3 h resulted in a significant reduction in steatosis [ 40 ], indicating the protective effect of this drug on steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta and colleagues [ 38 ] were the first to propose that the activation of the hepatic GLP-1R plays a direct role in reducing hepatic steatosis in vitro through modulation of the elements of the insulin signaling pathway. Recently, we and others [ 39 , 40 , 41 ] have shown that the GLP-1R agonist Exendin-4 (Ex-4) reduces the fat content in an in vitro cell model of steatosis by inhibiting hepatic lipogenesis through activation of β-catenin signaling and modulation of the expression of several lipogenesis genes. In addition, β-catenin might also mediate the effect of Ex-4 on ameliorating hepatic steatosis induced by a high fructose diet in rats [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…We further labeled the nuclei by incubating the cells with 1 μM DAPI for 1 min. After a final wash with PBS, we mounted the coverslips on microscope slides used for imaging on a Zeiss LSM 870 confocal microscope, as we reported recently 45 . To analyze the images, we used ImageJ software (version 1.8.0, NIH, USA).…”
Section: Methodsmentioning
confidence: 99%